Ladder of power and freedom - Petesch, Patti (International Maize and Wheat Improvement Center, 2018)
Presented by Patti Petesch (GENNOVATE), as part of the Annual Gender Capacity Development Workshop hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 27-28 September 2018.